Evolutionary potential varies across populations and traits in the neotropical oak Quercus oleoides. (15th October 2018) - Ramírez-Valiente, José A; Etterson, Julie R; Deacon, Nicholas J; Cavender-Bares, Jeannine
Abstract: Heritable variation in polygenic (quantitative) traits is critical for adaptive evolution and is especially important in this era of rapid climate change. In this study, we examined the levels of quantitative genetic variation of populations of the tropical tree Quercus oleoides Cham. and Schlect. for a suite of traits related to resource use and drought resistance. We tested whether quantitative genetic variation differed across traits, populations and watering treatments. We also tested potential evolutionary factors that might have shaped such a pattern: selection by climate and genetic drift. We measured 15 functional traits on 1322 1-year-old seedlings of 84 maternal half-sib families originating from five populations growing under two watering treatments in a greenhouse. We estimated the additive genetic variance, coefficient of additive genetic variation and narrow-sense heritability for each combination of traits, populations and treatments. In addition, we genotyped a total of 119 individuals (with at least 20 individuals per population) using nuclear microsatellites to estimate genetic diversity and population genetic structure. Our results showed that gas exchange traits and growth exhibited strikingly high quantitative genetic variation compared with traits related to leaf morphology, anatomy and photochemistry. Quantitative genetic variation differed between populations even at geographical scales as small as a few kilometers. Climate was associated with quantitative genetic variation, but only weakly. Genetic structure and diversity in neutral markers did not relate to coefficient of additive genetic variation. Our study demonstrates that quantitative genetic variation is not homogeneous across traits and populations of Q. oleoides . More importantly, our findings suggest that predictions about potential responses of species to climate change need to consider population-specific evolutionary characteristics.